Petroleum Products Price Fluctuations and Economic Growth in Cameroon - Forgha, Njimanted Godfrey; Sama, Molem Christopher; Achuo, Elvis Dze (Growth, 2015)
Commodity exports have over the years been the main source of foreign exchange earnings to most developing countries. This is especially the case with crude oil producing countries such as Cameroon since the discovery of oil in the late 1970s. However, as evident in the economic crises era of the mid 1980s, this exposes the commodity dependent country to heavy external shocks such as price fluctuations which affect the level of growth of the country. It is in this light that this study was conducted to examine the effect of petroleum products (crude oil) price fluctuations on the economic growth of Cameroon. Secondary data from1980 to 2013 were used to estimate the coefficients of the ordinary least square technique used to analyse the dependency between the dependent and independent variables of the phenomenon. The results obtained reveal that petroleum product prices have a positive significant effect on the economic growth of Cameroon, while the volume of trade to GDP (openness) and real interest rate have a negative significant effect on the economic growth of the country. Human factors (demand and supply imbalances, and interest rates) and natural factors (geographical location and resource endowment) are the principal causes of variations in the prices of petroleum products among different regions. From these, it is suggested that for Cameroon to benefit from the global trade process by opening up to the rest of the world, the revenue generated from crude oil exploitation should be re-directed towards investment in both human and physical capital so as to enhance the productive capacity of the nation, especially in the manufacturing and transport sectors.